Expanding horizons for clinical applications of chloroquine, hydroxychloroquine, and related structural analogues - Ashutosh M Shukla; Aparna Wagle Shukla (BioExcel Publishing Ltd, 2019)
Several experimental and clinical studies have transformed the traditional antimalarial role of chloroquine (CHQ) and related structural analogues to potent therapeutic agents for a host of nonmalarial indications. The expanding clinical applicability for these drugs includes rheumatological and cardiovascular disorders (CVD), chronic kidney disease (CKD), oncology, and a variety of nonmalarial infections. These clinical advancements are primarily related to pleiotropic pharmacological actions of these drugs, including immunomodulation, anti-inflammatory properties, and capabilities of inducing autophagy and apoptosis at a cellular level. Historically, many clinical benefits in nonmalarial indications were first recognized through serendipitous observations; however, with numerous ongoing systematic clinical studies, the clinical horizons of these drugs have a promising future.